1993
DOI: 10.1002/jsfa.2740610116
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of emulsified triglycerides

Abstract: Nucleation and crystal growth process of triglycerides in water emulsions composed of trimyristin (c14:O) admixed with 0, 40, and 80 ml litre-' trilaurin (c12:O) (expressed v per total v emulsion) were followed with NMR (nuclear magnetic resonance) and DSC (differential scanning calorimetry). Mathematical analysis of the time dependence of the phase changes and thermal data distinguished two distinct 'apparent' kinetic phases. These phases were tentatively referred to as nucleation and crystal growth. With 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Firstly, the lower viscosity of 0.2 % SFW/1 % PA emulsion could affect the particle properties of polymorphism and polydispersion. Some authors showed that the esters of some alcohols with an odd number of carbon atoms presented different morphologies depending on the cooling conditions, the wax concentration in the oil [24][25][26][27] droplet size, and the nature of the emulsifier [28][29][30]. It is often assumed that an emulsified fat crystallizes via a homogeneous mechanism, but in fact homogeneous nucleation will only dominate if the particle size is reduced, so there is much less than one nucleus per droplet and hence the dominant mechanism may depend on the composition and purity of the fat as well as the structure of the emulsion.…”
Section: Stabilitymentioning
confidence: 99%
“…Firstly, the lower viscosity of 0.2 % SFW/1 % PA emulsion could affect the particle properties of polymorphism and polydispersion. Some authors showed that the esters of some alcohols with an odd number of carbon atoms presented different morphologies depending on the cooling conditions, the wax concentration in the oil [24][25][26][27] droplet size, and the nature of the emulsifier [28][29][30]. It is often assumed that an emulsified fat crystallizes via a homogeneous mechanism, but in fact homogeneous nucleation will only dominate if the particle size is reduced, so there is much less than one nucleus per droplet and hence the dominant mechanism may depend on the composition and purity of the fat as well as the structure of the emulsion.…”
Section: Stabilitymentioning
confidence: 99%
“…Owing to its experimental simplicity and its potential to follow the process in situ, this NMR technique seems to be superior to the previous radiolabeling method. NMR spectroscopy (typically 1 H) is frequently used for the determination of total solids content in oil mixtures (5)(6)(7)(8), and 1 H NMR imaging has been applied to visualize crystallization in lipid dispersion (9)(10)(11). Deuterium ( 2 H) NMR also has been applied to characterize the molecular mobility in and the transitions between the αand β-crystalline states of PPP (12).…”
mentioning
confidence: 99%
“…pNMR is a standard method for the measurement of solid fat content 63 and whilst water reduces accuracy methods have been developed for the measurement of solid fat content in food emulsions [64][65][66] . In comparison, ultrasound is more sensitive and accurate at low solid contents, however it becomes increasingly inaccurate at later stages in crystal growth where crystal networks are developing.…”
Section: A Brief Comparison Between Ultrasound Dsc Infra Red and Nmrmentioning
confidence: 99%